From ORCID to Google Scholar: How to manage your Digital Academic Identity - Romo, Ignacio (My University, 2026)
This training session provides a practical introduction to managing a coherent and effective digital academic identity across major scholarly platforms, including ORCID, Scopus, Web of Science, and Google Scholar. It outlines the importance of persistent identifiers for ensuring accurate attribution, enhancing visibility, and supporting institutional evaluation processes. Participants learn how to create, update, and synchronize their author profiles; resolve common issues such as duplicate records and misattributed publications; and maintain consistent information regarding name variants and affiliations. The session also highlights best practices for linking platforms through ORCID to automate updates and reduce administrative workload. Overall, the training emphasizes the growing relevance of digital identity management in the contemporary research ecosystem and provides actionable guidance for maintaining accurate and up-to-date academic profiles.
Keywords: 62 Ciencias de las Artes y las Letras; ODS 4 - Educación de calidad